Toroidal flow measurements of impurity ions in QUEST ECH plasmas using multiple viewing chords emission spectroscopy. (March 2021) - Yoneda, N.; Shikama, T.; Hanada, K.; Mori, S.; Onchi, T.; Kuroda, K.; Hasuo, M.; Ejiri, A.; Matsuzaki, K.; Osawa, Y.; Peng, Y.; Kawamata, Y.; et al.
Highlight: An inversion method composed of Abel inversion and "shell model". Dependence of toroidal flow on magnetic configurations. Flow in the same direction as that of Pfirsch-Schlüter flow in SOL regions. Abstract: A spectroscopic system with multiple viewing chords was developed for QUEST (Q-shu University Experiment with Steady-State Spherical Tokamak) to measure the spatial distribution of ion toroidal velocities in discharges sustained by electron cyclotron resonance heating (ECH). Twenty-four viewing chords were aligned in the midplane and C III emission line spectra were measured for three types of ECH discharge under different magnetic field configurations. By applying an inversion method to the measured spectra, we evaluated the radial distributions of C 2+ ion emissivity, temperature, and toroidal velocity. The error in the evaluated velocity was estimated to be less than 5 km/s. It was found that the velocity depends on the magnetic field configuration.